EXPLORING THE DYNAMIC EFFECTS OF FAIR VALUE ACCOUNTING ON THE PERFORMANCE METRICS OF CONSUMER GOODS FIRMS IN NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
Fair value accounting (FVA) has emerged as a pivotal framework in financial reporting, promising enhanced transparency but introducing volatility in performance metrics. This study investigates the dynamic effects of FVA on the financial performance of consumer goods firms in Nigeria, a sector critical to the nation’s economy. Using a mixed-methods approach, primary data were collected via surveys and interviews from 120 financial managers and accountants across 30 consumer goods firms in Lagos and Abuja. Findings reveal that FVA improves asset valuation accuracy and investor confidence but increases earnings volatility, impacting key performance metrics like return on assets (ROA) and earnings per share (EPS). Demographic analysis shows participants were 65% male, 35% female, predominantly aged 30–45, with 70% holding advanced accounting qualifications. Challenges include high implementation costs, technical complexity, and market illiquidity, particularly in Nigeria’s volatile economy. The study advocates for tailored training, robust valuation models, and regulatory support to mitigate FVA’s adverse effects. This research contributes to the discourse on FVA’s applicability in emerging markets, offering a framework for aligning accounting practices with firm performance. Recommendations include capacity building and collaboration with regulatory bodies to enhance FVA adoption.